Spatial variability of soft-bottom macrobenthic communities in northern Sicily (Western Mediterranean): Contrasting trawled vs. untrawled areas. (December 2016) - Romano, C.; Fanelli, E.; D'Anna, G.; Pipitone, C.; Vizzini, S.; Mazzola, A.; Badalamenti, F.
Abstract: This study examines the impact of bottom trawl fishing on the macrobenthic communities inhabiting the coastal terrigenous mud off the northern coast of Sicily (Western Mediterranean). Two intensely trawled gulfs were compared with two gulfs from which trawling has been excluded for 15 years. The results show a significant effect of trawling on the faunal assemblage and when comparing the mean biomass and the whole isotopic composition of the benthic communities. A similar pattern, although not significant, was found for total abundance, biomass, production/biomass ratio and diversity. Higher abundance and lower biomass were found in the untrawled areas, attributable to the presence of more numerous yet smaller individuals, possibly a consequence of more abundant larger predators that are not removed by trawling, and consequent higher predatory pressure on the benthic macrofauna. The SIMPER analysis evidenced a dominance of burrowing deposit feeding worms (Paraonidae and Cossuridae) in trawled areas, as a result of increased mechanical alteration and hence more organic matter available as food. In contrast, the response to trawling as drawn by the use of trophic markers (i.e., stable isotopes) was less clear. While δ 15 N of benthic taxa did not vary significantly between untrawled and trawled areas, δ 13 C was higher in trawled areas possibly due to high sediment resuspension and consequent intense microbial activity. Mixing models confirmed higher reliance to a detritus-based food web for benthic organisms in the trawled areas. Standard Ellipse Areas (SEAc) as a measure of community niche width were slightly larger in trawled areas, likely due to higher generalism triggered by alteration/removal of the original benthic community. Highlights: The impact of bottom trawling on macrobenthos has been studied in trawled and untrawled gulfs. Higher abundance and lower biomass were found in the untrawled areas. Increased fish biomass in the untrawled areas may have consumed larger benthic prey individuals. No effect of trawling on δ 15 N values and trophic level of benthic taxa was found. δ 13 C values were higher in trawled areas possibly due to high sediment resuspension and greater dependence to benthic food web was here observed.